Desvendando as fezes de felinos - Frasnelli, Julyenne Christynne Escrivani (2023)
Feline excreta have been the object of study for years by several researchers. This survey recorded the biological and behavioral aspects of the feces of this group of animals. Why is feces buried at certain times and left exposed at others? What are the meanings? Does domestication and human influence affect this act as well? The first chapter of this work aims to systematize this knowledge and answer the questions presented. In addition to a critical synthesis of this theme, differences and sanitary interference, another question: do owners know the atavistic needs of domestic cats and do they provide an environment endowed with well-being and safety? With that in mind, the second chapter of this work was developed on the theme of a manual with informal language, to teach cat lovers about their primary needs in urban homes, as well as the best way to interact with them, targeting their potential mesopredator species. In the third chapter, we developed a didactic material in a playful way for children between six and seven years old, demonstrating the different roles of feline feces, elucidating the differences between felines that are close (domestic cats) and free-living ones. This work aims to contribute to awareness, knowledge and respect for the needs of cats (including free-living ones) and to awaken interest in the conservation of this animal group.